2020
DOI: 10.3390/diagnostics10050319
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Tests in Detecting SARS-CoV-2 Infection: A Meta-Analysis

Abstract: The emergence of Coronavirus disease 2019 (COVID-19) caused by SARS-CoV-2 made imperative the need for diagnostic tests that can identify the infection. Although Nucleic Acid Test (NAT) is considered to be the gold standard, serological tests based on antibodies could be very helpful. However, individual studies are usually inconclusive, thus, a comparison of different tests is needed. We performed a systematic review and meta-analysis in PubMed, medRxiv and bioRxiv. We used the bivariate method for meta-analy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
226
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(240 citation statements)
references
References 81 publications
10
226
3
1
Order By: Relevance
“…A combined IgG/IgM test displayed better sensitivity than measuring either antibody type alone with ELISA tests being more sensitive than lateral flow immunoassays. 63 A recent study found high sensitivity and specificity of the RBD for antibody detection and its strong association with SARS-CoV-2 neutralizing antibodies. 59 Studies are ongoing to determine the clinical performance characteristics of various antibody tests across different platforms.…”
Section: Serology Testingmentioning
confidence: 98%
“…A combined IgG/IgM test displayed better sensitivity than measuring either antibody type alone with ELISA tests being more sensitive than lateral flow immunoassays. 63 A recent study found high sensitivity and specificity of the RBD for antibody detection and its strong association with SARS-CoV-2 neutralizing antibodies. 59 Studies are ongoing to determine the clinical performance characteristics of various antibody tests across different platforms.…”
Section: Serology Testingmentioning
confidence: 98%
“…immunoassays (LFIAs) offer the potential for relatively cheap tests that are easily distributed and can be either self-administered or performed by trained healthcare workers. However, despite manufacturers' claims of high sensitivity and specificity, reported performance of these assays has been variable [3][4][5][6][7][8][9] and their use is limited to date. In the UK, the Medicines and Healthcare Products Regulatory Agency (MHRA) requires that clinical sensitivity and specificity must be determined for each claimed specimen type, and that sample equivalence must be shown.…”
Section: Respiratory Infectionmentioning
confidence: 99%
“…More importantly, a serological test could capture previous asymptomatic infections and help to assess the immune status of a subject and finally estimate herd immunity. 12 Worldwide, several countries are going to ease the restriction measurements after the initial COVID-19 wave faded away. However, the SARS-CoV-2 seroprevalence is still low in the population, and herd immunity has not been developed.…”
Section: Significance Of This Studymentioning
confidence: 99%